2012
DOI: 10.1029/2011jd016587
|View full text |Cite
|
Sign up to set email alerts
|

High vertical resolution analyses of gravity waves and turbulence at a midlatitude station

Abstract: [1] We proposed a broad spectral data-analyzing method to study the altitude and seasonal variability of gravity wave (GW)-associated dynamics in the lower atmosphere at a midlatitude by using the radiosonde data from Miramar Nas (32.87°N, 117.15°W), California, during 1998California, during -2008. Generally, the presented primary statistical features of GW parameters and their seasonal variation are consistent with previous radiosonde observations by using the conventional hodograph analysis method based on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
109
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 39 publications
(116 citation statements)
references
References 89 publications
7
109
0
Order By: Relevance
“…In the troposphere, the amplitude varies from 0.02 to 0.05 m 2 s −2 cycle −1 km −1 , while a much larger spectral amplitude can be observed in the lower stratosphere, with the largest amplitude greater than 0.2 m 2 s −2 cycle −1 km −1 occurring in January 2002. In the troposphere, the spectral amplitudes show a regular annual cycle, with a larger (smaller) value in winter (summer), which is consistent with the gravity wave energy seasonal variation at middle latitude (Zhang et al, 2012). These spectral amplitudes are comparable to those radar observations in the lower atmosphere (Larsen et al, 1986(Larsen et al, , 1987Fritts and Chou, 1987) but obviously smaller than the lidar observations in the mesopause region (Gardner et al, 1998).…”
Section: Vertical Wind Fluctuation Spectrasupporting
confidence: 74%
See 4 more Smart Citations
“…In the troposphere, the amplitude varies from 0.02 to 0.05 m 2 s −2 cycle −1 km −1 , while a much larger spectral amplitude can be observed in the lower stratosphere, with the largest amplitude greater than 0.2 m 2 s −2 cycle −1 km −1 occurring in January 2002. In the troposphere, the spectral amplitudes show a regular annual cycle, with a larger (smaller) value in winter (summer), which is consistent with the gravity wave energy seasonal variation at middle latitude (Zhang et al, 2012). These spectral amplitudes are comparable to those radar observations in the lower atmosphere (Larsen et al, 1986(Larsen et al, , 1987Fritts and Chou, 1987) but obviously smaller than the lidar observations in the mesopause region (Gardner et al, 1998).…”
Section: Vertical Wind Fluctuation Spectrasupporting
confidence: 74%
“…According to the GW theory, the vertical wavelength will decrease with the decrease in the intrinsic frequency, thus leading to the energy transportation from large vertical scale to smaller scale, in turn yielding a shallower spectrum in winter in the lower stratosphere. Radiosonde observations of gravity waves at the same station (Zhang et al, 2012) also indicated that GWs in the lower stratosphere have shorter vertical wavelengths compared with those in the troposphere. As a result, the horizontal wind spectral slopes have evident seasonal variations, with less negative values in winter.…”
Section: Horizontal Wind Fluctuation Spectramentioning
confidence: 98%
See 3 more Smart Citations